The Assessment of Nutritional Status of Pregnant Women, Age, Occupation and Risk Factors for Pregnancy Due - Wariyaka, Melinda Rosita; Wea, Maria Fatima Saga (Ahmar Metastasis Health Journal, 2025)
The nutritional status of pregnant women is a crucial factor that impacts the health of both the mother and fetus during pregnancy, childbirth, and the postpartum period. This study aims to describe and analyze the relationships between the nutritional status of pregnant women, pregnancy risk groups, and the demographic characteristics of pregnant women in Kupang City. The design of this study was descriptive-analytic with a quantitative approach. Data were collected from most health centers in Kupang City in March 2024 through pre-pregnancy body mass index (BMI) measurements, pregnancy risk scores based on the Poedji Rochjati Score Card (PRSC), and demographic data of pregnant women. Chi-Square and Fisher's Exact Test were used to analyze the relationship between variables. Of the 140 respondents, the majority of pregnant women had normal nutritional status (79%), were at reproductive age (69%), and belonged to the low pregnancy risk group (74%). The analysis results showed a significant relationship between the nutritional status of pregnant women and age and pregnancy risk group (p<0.05), but no significant relationship between nutritional status and employment status or education level. In conclusion, good nutritional status before pregnancy correlates with lower reproductive age and pregnancy risk, so it is important for promotive and preventive efforts to focus on improving nutrition from adolescence and before pregnancy.